Customs House Agents Perspective on Effectiveness of Container Freight Stations, Chennai - Preetha Subrahmanyan; S. Subhashini (International Journal of Supply Chain Management, 2018)
A key factor in determining the trade volume is the efficiency of the cargo handling capacity of the ports. Container Freight Stations forms a major infrastructural component which primarily contributes to the decongestion of ports at the terminals. It is considered as an extension of department of customs. As India has improved its trade environment, development of ports, the volume of trade has increased over the years. The containerization of cargo has increased the role of CFS in India. CFS are the integral part of the EXIM supply chain. Custom House Agents and importers have some grievances such as the delay in the movement of cargo which would in turn increase the demurrage incurred on the importers, lack of infrastructure facilities, modern container handling equipment. Indias EXIM trade is fast growing and for managing and sustaining the growth, it is very essential to enhance the infrastructure facilities, modern cargo handling equipment. The purpose of the study is to analyse the important criteria in the selection of a CFS, the association of problems and satisfaction of the Customs house agents. SPSS 21 is used to perform the MANOVA, ANOVA and Correlation analysis. The results revealed that there is a significant effect of number of shipping bills on location, safety and quick clearance, difference of opinion on satisfaction between importers and exporters and a negative association between the problems in the CFS and satisfaction. The study also identified that quick clearance, modern cargo handling equipments and location are the major criteria in the selection of the CFS. Keywords: Container Freight Stations, Customs House Agent, EXIM, CHA, LOGISTICS FIRMS.